Pengembangan Ekowisata Berkelanjutan Melalui Digitalisasi Pemasaran Berbasis Website dan Media Sosial: Pengabdian - Neffi Sulkaisi; Herisvan Hendra; Meri Rahmania; Bunga Rahmatul Ulia; Mela Agustia (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program is based on the low visibility of the ecotourism potential of Nagari Sisawah, managed by Pokdarwis. The program aims to enhance tourism competitiveness through digitalization, service excellence training, and website and social media management. The implementation method includes participatory-based socialization, training, mentoring, and evaluation. The results showed increased Pokdarwis capacity in managing tourism safety information and digital marketing, as well as greater engagement of local youth in digital-based creative economic activities.